The electrolarynx: voice restoration after total laryngectomy - Kaye R (Dove Medical Press, 2017)
Rachel Kaye,1 Christopher G Tang,2 Catherine F Sinclair3 1Department of Otolaryngology, New York Center for Voice and Swallowing Disorders, New York, NY, 2Department of Otolaryngology, Kaiser Permanente San Francisco Medical Center, San Francisco, CA, 3Department of Otolaryngology, Mount Sinai Icahn School of Medicine, New York, NY, USA Abstract: The ability to speak and communicate with one’s voice is a unique human characteristic and is fundamental to many activities of daily living, such as talking on the phone and speaking to loved ones. When the larynx is removed during a total laryngectomy (TL), loss of voice can lead to a devastating decrease in a patient’s quality of life, and precipitate significant frustration over their inability to communicate with others effectively. Over the past 50 years there have been many advances in techniques of voice restoration after TL. Currently, there are three main methods of voice restoration: the electrolarynx, esophageal speech, and tracheoesophageal speech through a tracheoesophageal puncture (TEP) with voice prosthesis. Although TEP voice is the current gold standard for vocal rehabilitation, a significant minority of patients cannot use or obtain TEP speech for various reasons. As such, the electrolarynx is a viable and useful alternative for these patients. This article will focus on voice restoration using an electrolarynx with the following objectives: 1) To provide an understanding of the importance of voice restoration after total laryngectomy. 2) To discuss how the electrolarynx may be used to restore voice following total laryngectomy. 3) To outline some of the current electrolarynx devices available, including their mechanism of action and limitations. 4) To compare pros and cons of electrolaryngeal speech to TEP and esophageal speech. Keywords: total laryngectomy, voice restoration, electrolarynx, esophageal speech, tracheoesophageal puncture, silent speech, electrolarynx mechanics